Research of foreign experience in the functioning of the waste recycling system (on the example of khujand, tajikistan) ("Journal "U". Economy. Management. Finance.", 2022)
The article considers an enterprise for working with garbage waste in the city of Khujand, Tajikistan. It is determined that now the maintenance of the sanitary condition of the city is the main task of the organization of the State Unitary Enterprise "Sanitary Transport Service of Khujand". The main problem areas of management at the enterprise of the State Unitary Enterprise "Khujand Sanitary and Transport Service" have been identified and directions of actions to eliminate problems have been proposed. The main consumers of the organization's services are identified, and related issues are formulated. The organizational and staff structure is given and the internal barriers to the development and functioning of the organization are analyzed. It is revealed and substantiated that the operating conditions and the existing problems of the State Unitary Enterprise "Khujand Sanitary Transport Service" are also due to insufficient support from the authorities. The necessity of improving the management system and the development of the organization based on a set of measures, including activities to minimize environmental and economic risks and increase the level of safety of technological processes and occupational safety, has been identified.
Keywords: analysis; risk; ecology; waste; waste disposal; waste recycling system; landfill; sanitary service; working conditions; management processes; finance